2021
DOI: 10.3390/biology10111198
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Release of Mercury in the Lichen Evernia prunastri (L.) Ach

Abstract: This study investigated the dynamics of the accumulation and release of Hg2+ in lichens, using Evernia prunastri (L.) Ach. as a model species. Thalli were incubated with solutions containing 1, 10, and 100 µM Hg2+ and then exposed for 1, 2, 3, 6, 12, 18, and 24 months at the Botanical Garden of the University of Siena (a location free from local Hg sources). Lichen samples accumulated Hg proportionally to the exposure concentration, and after the exposure, reductions over time were evident, already starting fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
(55 reference statements)
1
3
0
Order By: Relevance
“…Owing to the low Hg amount in Evernia prunastri mentioned above and its soft thalli suitable for biochemical extraction, we selected this species for subsequent investigation focused on the toxicity of exogenous Hg and cross-talk with nitric oxide (see representative photo of Evernia thalli in Supplementary Figure S1 ). Total Hg content was not affected by SNP co-application, with an average value of 2.4 mg Hg/g DW, which is similar to data reported by Vannini et al [ 13 ] who also found over 2 mg Hg/g DW in the same species after 1 h of immersion in 100 µM Hg solution, as did we ( Figure 1 ). Lichen Ramalina farinacea , with similar fruticose thalli exposed to 100 µM Cd under identical exposure conditions, also contained close to 2 mg Cd/g DW [ 24 ], while terrestrial lichens Cladonia and Peltigera , exposed to 100 µM Hg under similar exposure conditions, contained over 1 mg Hg/g DW [ 12 ]; therefore, the sorption of metals seems to be affected by the applied concentration mainly.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Owing to the low Hg amount in Evernia prunastri mentioned above and its soft thalli suitable for biochemical extraction, we selected this species for subsequent investigation focused on the toxicity of exogenous Hg and cross-talk with nitric oxide (see representative photo of Evernia thalli in Supplementary Figure S1 ). Total Hg content was not affected by SNP co-application, with an average value of 2.4 mg Hg/g DW, which is similar to data reported by Vannini et al [ 13 ] who also found over 2 mg Hg/g DW in the same species after 1 h of immersion in 100 µM Hg solution, as did we ( Figure 1 ). Lichen Ramalina farinacea , with similar fruticose thalli exposed to 100 µM Cd under identical exposure conditions, also contained close to 2 mg Cd/g DW [ 24 ], while terrestrial lichens Cladonia and Peltigera , exposed to 100 µM Hg under similar exposure conditions, contained over 1 mg Hg/g DW [ 12 ]; therefore, the sorption of metals seems to be affected by the applied concentration mainly.…”
Section: Resultssupporting
confidence: 92%
“…Lichens are not plants, but lichenized fungi with their body (thallus) typically formed by the symbiotic association between fungus and green alga. Despite more common works focused on the use of lichens for biomonitoring of metallic pollution including the occurrence of Hg [ 6 , 7 , 8 , 9 , 10 , 11 ], physiological studies are rare [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the use of biochar in the environmental field concerns both the reduction of PTE mobility in soils to increase the edibility of crop products [ 28 , 29 ] and the removal of heavy metals from wastewater [ 31 , 32 ]. However, based on the results obtained in this study, its ability to provide information on the environmental availability of heavy metals such as Cd should not be ruled out, especially when it comes to water bodies.…”
Section: Resultsmentioning
confidence: 99%
“…Biochar (BC), the by-product of the pyrolysis of organic materials (often wood) for bioenergy production, is now attracting considerable attention, from an environmental perspective, as a strategy to stabilize PTEs in soils [ 27 , 28 , 29 ], thereby enabling their remediation [ 30 ]; as a tool for filtering contaminated water and air [ 31 , 32 , 33 ]; and as a sustainable strategy for agricultural purposes [ 34 , 35 ]. Despite these diverse applications, the potential of BC for environmental biomonitoring has been surprisingly underexplored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation